Burden of Clostridium difficile on the Healthcare System - Dubberke, Erik R. (Oxford University Press, 2012)
There are few high-quality studies of the costs of Clostridium difficile infection (CDI), and the majority of studies focus on the costs of CDI in acute-care facilities. Analysis of the best available data, from 2008, indicates that CDI may have resulted in $4.8 billion in excess costs in US acute-care facilities. Other areas of CDI-attributable excess costs that need to be investigated are costs of increased discharges to long-term care facilities, of CDI with onset in long-term care facilities, of recurrent CDI, and of additional adverse events caused by CDI.